Visible‐Light‐Induced Intramolecular Double Dearomative Cycloaddition of Arenes - Zhu, Min; Xu, Hao; Zhang, Xiao; Zheng, Chao; You, Shu‐Li (Angewandte Chemie International Edition, 2021)
Herein we report visible‐light‐induced intramolecular double dearomative cycloaddition of arenes. Compared with the well‐known photodimerization of arenes under ultraviolet irradiation, the current reactions are carried out under mild conditions and feature wide substrate scope. A large array of structurally‐diverse polycyclic indoline derivatives is afforded in high yields (up to 98 %) with exclusive diastereoselectivity (>20:1 dr) via dearomative [4+2] or [2+2] pathway. The visible‐light‐induced intramolecular double dearomative cycloaddition of arenes is reported. The reactions are carried out under mild conditions and feature a wide substrate scope. A large array of polycyclic indoline derivatives is afforded via dearomative [4+2] or [2+2] cycloaddition pathways in high yields with exclusive diastereoselectivity.